Teens are hungry for what? Determinants of food choice (Research, Society and Development, 2021)
Adolescence is defined chronologically by the World Health Organization (WHO) to characterize individuals who are between 10 and 19 years old. This study aimed to carry out a narrative review on the dietary profile of adolescents. This is a qualitative research, using a bibliographic analysis of a narrative character carried out by consulting online research databases: Scielo (Scientific Electronic Library OnLine), BVS (Virtual Health Library), and Academic Google, where the research was carried out with the time frame from 2016 to 2021. As a result, it was found that the diet of adolescents is mostly composed of fat, sodium and simple sugars, which are accompanied by a sedentary lifestyle. Adolescents' diet is basically composed of foods rich in sugar and high in fat, low consumption of fruits and vegetables, which favors weight gain above the ideal and greater likelihood of developing Chronic Non-Communicable Diseases. It is concluded in this aspect, adolescents have mainly consumed processed and ultra-processed industrialized products, decreasing their physical health and psychology and increasing the problem of obesity worldwide. These products have affordable prices and are widely publicized in the media, giving the false feeling that they can be consumed freely without causing harm to health.